Biomedical research nowadays: questioning society as a whole - Rovaletti, María Lucrecia (Acta Bioethica, 2003)
The second biomedical revolution puts into question human society as a whole inasmuch as it gives to human being the dominion over three fundamental systems, namely: reproduction, genetics, and the nervous system. Current experiment assays go beyond either health protection or health recovery, thus allowing new techniques to be challenged in the sense that they may modify the evolution of species; furthermore they may modify humans as a species. On no account, however, are we suggesting simply that some control program on science be implemented, nor are we willing to sow mutual suspicions likely to generate an endless quarrel on scientific advance. To progress towards an actual problem solving process coupled to a cooperation between scientific culture and human values, it is necessary that research on people must be transformed into researching with people. To which extent, however, medical research is in a position to envision new alliances between scientific tasks and human demands? Setting up an expanded scientific community able and willing to present new social actors with a collective appropriation of knowledge is an urgent commitment to be considered thoroughly.